صکوک: تعارف، اقسام،تاریخ، اہمیت اور معاشی ترقی میں اس کا کردار: Sukuk: Introduction, Types, History & Importance and its role in Economic Development - Dawood, Dr.Kaleem Ullah (MEI, 2023)
Abstract: Sukuk has become an integral part of the Islamic economic system and Islamic financial institutions because of its need and importance. Sukuk is a financial instrument to raise the necessary capital at the government level for infrastructure projects, to offset losses in the financial budget, and to pay off domestic and international loans, and it is the best means to invest additional capital for Islamic banks and takaful companies. Moreover, corporations can raise capital from sukuk for construction purposes, acquiring heavy machinery, trade expenses, or raise funds for socio-economic projects. However, what still remains a topic of research is that some scholars of the modern era have made confusion about its origin and history as they considered it is as the same as was widespread in the early Islamic era of the Holy Prophet (S.A.W.S) and Khulafa e rashideen. In this article, I discussed the whole matters that pertain to the origin and history of modern sukuk, its kinds, importance, and its vital role in current Islamic financial system. And also illustrated the differences between the modern sukuk and the one for which this word was used in the early Islamic era.